Fabrication of a Cost-Effective in-House Electrode Assembly for Recording EEG and Behavioral Seizures in Unrestrained Rats - Yadav, Nitin; Mittal, Radhika; Chaudhary, Arzoo; Priya, Priya; Banerjee, Jyotirmoy; Dixit, Aparna Banerjee (Indian Journal of Pharmaceutical Education and Research, 2026)
Background: Electroencephalography (EEG) is a valuable tool in neuroscience research for analyzing epileptic seizures in animal models. However, the cost that comes with commercial electrode assemblies is a critical challenge, particularly in low- and limited-resource settings. Thus, developing an inexpensive but dependable substitute is critical for improving access to epilepsy pre-clinical research. Materials and Methods: The research article here discusses a systematic methodology for designing and developing a low-cost electrode system for EEG recording and behavioral seizure monitoring in freely moving rats. The electrode assembly utilizes readily available materials significantly reducing the costs without compromising the data integrity. The electrode fixation ensures stable signal acquisition with reduced signal loss in experiments. Results: The stability and performance of internally assembled electrode setup was evaluated during spontaneous and induced seizures in rat models of epilepsy. Our research findings demonstrate that these electrodes were reliable for repeatedly detecting the epileptiform activity, in regards to signal quality and seizure evaluation accuracy. Conclusion: The proposed low-cost electrode structure offers a viable alternative to costly commercial arrangements, making EEG-based seizure analysis more accessible to researchers working within budget restrictions or in limited resource facilities. By providing high-quality EEG recordings and behavioural tests, this method contributes to a better understanding of seizure pathophysiology and supports preclinical research on epilepsy employing animal models.
Keywords: Electroencephalography (EEG); Seizures; Electrode Configuration; Wired EEG; Low-Cost Electrode